2013
DOI: 10.1017/s1049096512001242
|View full text |Cite
|
Sign up to set email alerts
|

Communicating in 140 Characters or Less: Congressional Adoption of Twitter in the 111th Congress

Abstract: Recently, new electronic technologies have supplemented older mechanisms of communication between members of Congress and their constituents. These technologies have enhanced members' options for communication, both with constituents and other interested parties. This research examines member use of one specific electronic communication medium: Twitter. Using original data to examine patterns of use, two models predict the probability of a member adopting Twitter based on political, personal, and district-leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
58
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 26 publications
2
58
0
5
Order By: Relevance
“…Finally, previous findings regarding the impact of age on social media use are unsurprising: Older politicians are less likely to be active on social media (Lassen & Brown, 2011;Lawless, 2012;Peterson, 2012;Straus et al, 2013).…”
Section: Congress and Other Social Mediamentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, previous findings regarding the impact of age on social media use are unsurprising: Older politicians are less likely to be active on social media (Lassen & Brown, 2011;Lawless, 2012;Peterson, 2012;Straus et al, 2013).…”
Section: Congress and Other Social Mediamentioning
confidence: 97%
“…Their research found that state legislative candidates running in districts with large numbers of constituents older than 55 years were less likely to use the Internet to contact supporters, and less likely to create campaign websites. Straus et al (2013) found that the distance between a member's district and Washington also might be an important factor in explaining social media presence as well. In some of their models, distance influenced the probability that a member adopted Twitter, with the intuition being that members representing communities located further away from the capital were more likely to use social media because it can function as a useful means of keeping in touch with the folks back home when traveling often to their district might not be possible.…”
Section: Congress and Other Social Mediamentioning
confidence: 98%
“…Social media adoption by politicians has been well documented in recent years (e.g., Gainous and Wagner 2014;Gulati and Williams 2015;Straus et al 2013;StromerGalley 2014). While Twitter has been a popular platform for social media politicking, 1 Facebook boasted the highest usage rate by politicians and candidates in the 2010 and 2012 elections.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, just over 50 % of members of Congress(Straus et al 2013) and major party candidates(Gainous and Wagner 2014) had a Twitter account. 2 Sharon Angle (R-NV) is not included in the sample.…”
mentioning
confidence: 99%
“…In fact, recent research indicates that a large majority of representatives and senators are very active in social media (e.g. Straus et al 2013) while also suggesting that the target audience of social media messages may be di↵erent than the audience of newsletters, TV messages or press releases (Barbera 2014). This begs the question Do members of Congress adopt the same communication strategy independently of the media channel they use to communicate?…”
Section: Introductionmentioning
confidence: 99%